Modeling of Solar Updraft Tower Power Plants: A Review - Mustafa, Ayad T. (Journal of Advanced Mechanical Engineering Applications, 2022)
Solar updraft tower power plants, or SUTPP, are thermal power plants consisting of three parts: a solar collector, a power conversion unit (turbine), and a solar chimney. Different configurations of SUTPP models were presented in the previous studies. However, the type used in the modelling of SUTPP elements with the variables used is not highlighted. Therefore, a modelling approach to improving or investigating the SUTPP is reviewed in the present work. Modeling can be broken down by which part of the solar chimney power plant was used. Predictive, thermal, and simulation models were used for the solar collector and chimney, while analytical and simulation models were used for the wind turbine power unit. used in the modelling have been addressed, such as airflow velocity, the temperature distribution in the collector, air temperature and pressure leaving the collector, output temperature from the collector, coefficient of heat transfer by convection, power produced, SCPP efficiency, and the thrust factor of the wind turbine. The review study is of great importance to maximize the power produced and efficiency by comparing multiple models.